Kajian Pemanfaatan Ruang Terhadap Sistem Transportasi ( Studi Kasus: Jl Pahlawan Revolusi Kel Pondok Bambu Jakarta - Prasetyo, Irwan; Triwicaksono, bayu; zefri, zefri (Journal of Urban and Regional Development Studies, 2023)
Population growth in East Jakarta City Administration has been very rapid since 2000 of 1,959,022 people and in 2017 reached 2,892,783 people with a population growth rate of 2.4% per year. With this population development will demand a service activity to fulfill the needs and allocation of space such as: trade and services, housing and housing, industrial zones, offices, education, health, transportation, green open space and others. In addition, the emergence of activities centers in East Jakarta including the Cililtan Wholesale Center (PGC), Jatinegara trade / services / Rawamangun / Klender / Housing Rebo market, government center in Cakung sub-district, Cakung Small Industrial Village, Pulao Gadung industry and warehousing center, center Klender, defense and security furniture at Cikeas, the center of cultural tourism (TMII). Arrangement of spatial allocation and zoning regulations in general and specifically in the corridor of Jalan Pahlawan Revolusi, Pondok Bambu Urban Village has been regulated in DKI Jakarta Regional Regulation No. 1 of 2014 concerning Detailed Spatial Planning for the city and Zoning Regulations 2014 – 2034. Based on current field facts related to the implementation of spatial use in the Heroes of the Revolutionary Road in the Pondok Bambu Kelurahan, the juxtaposition with the provisions in the DKI Jakarta RDTR and PZ Regional Regulation shows that: changes in land use and activities, discrepancies in spatial patterns, discrepancies in intensity of spatial use (KDB, KDH, GSB), the lack of space utilization permit (IMB). From this incident the use of space impacts on transportation systems such as (traffic generation, traffic congestion, modes of transportation). In addition, the implementation of spatial utilization is not yet optimal due to the lack of supervision and control of spatial use carried out by local governments along with community participation and the business world, or it could be that the quality of RDTR and PZ has not been operational in facing the very rapid development dynamics in the field